Sexual Consent Challenges Among GBMSM: Rates, Reasons, and Risk Factors - McKie, Raymond (Université d'Ottawa / University of Ottawa, 2025)
Gay, Bisexual, and other Men who have Sex with Men (GBMSM) experience disproportionately high rates of nonconsensual sexual experiences (NSEs), yet accurate prevalence estimates remain elusive due to inconsistent terminology and measurement limitations. This dissertation comprises two studies aimed at improving understanding and measurement of NSEs in GBMSM. Study 1 examined how GBMSM label and report NSEs, comparing self-identification with experiences assessed through behavioural indicators. Among a Canadian sample of 346 GBMSM, 64.5% endorsed a history of NSEs via a two-part question, while 66.8% reported such experiences on the Sexual Experiences Survey-Short Form Victimization. Demographic analyses revealed higher prevalence among trans men and People of Colour. Study 2 validated the Reasons for Consenting to Unwanted Sex Scale (RCUSS) using bifactor exploratory structural equation modeling. Results supported a multidimensional structure with three interpretable group factors - emotional, interpersonal, and contextual pressures - alongside a general factor. Together, these findings highlight the importance of nuanced, inclusive assessment tools and culturally responsive frameworks to better understand and address consent-related challenges in sexual minority populations. This research has critical implications for measurement, public health, and the development of interventions tailored to GBMSM's lived experiences with sexual consent negotiation and coercion.
Keywords: sexual consent; gay, bisexual men; sexual violence; minority stress